The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1101/215467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paternal grandparental exposure to crop failure or surfeit during a childhood slow growth period: Epigenetic marks on grandchildren’s growth, glucoregulatory and stress genes

Abstract: This latest in our series of papers describes transgenerational methylation related to midchildhood food availability in 19th century Överkalix, Sweden. Failed vs. bountiful crops differentially influenced methylation in grandchildren of paternal grandparents exposed to feast or famine during their Slow Growth Period (SGP), a sensitive period preceding the pre-pubertal growth spurt. In this case-study of 8 tracked 75-year old progeny with differential ancestral exposure, we found, in 40 posited gene ontology p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Among 146 male probands in these studies, the estimated mortality hazard ratios on paternal over- and undernutrition, respectively, were a statistically significant 1.70 and a statistically insignificant 1.11 (a magnitude similar to ours) ( 20 ). A follow-up of eight descendants of the Överkalix study found that different geneontology pathways were implicated in paternal and maternal line transmission of nutritional stress ( 40 ). Although sexual dimorphism in developmental origins of health and disease is little understood, it is considered an outcome of both genetics and epigenetics ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among 146 male probands in these studies, the estimated mortality hazard ratios on paternal over- and undernutrition, respectively, were a statistically significant 1.70 and a statistically insignificant 1.11 (a magnitude similar to ours) ( 20 ). A follow-up of eight descendants of the Överkalix study found that different geneontology pathways were implicated in paternal and maternal line transmission of nutritional stress ( 40 ). Although sexual dimorphism in developmental origins of health and disease is little understood, it is considered an outcome of both genetics and epigenetics ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also becomes apparent that epigenetic changes on the offspring can be mediated even in the early embryonic period, at a time when a couple does not know that they have conceived and are influenced by aspects of paternal behaviour, mediated by epigenetic effects on the sperm . The inheritance of cardiovascular and metabolic disease risk by epigenetic processes can be passed down to grand–offspring in both animal studies and human cohorts (see ), but the issue is controversial .…”
Section: Mechanisms Of Inheritance Of Cvd Riskmentioning
confidence: 99%